(untitled) (American Journal of Management, 2022)
The concepts of public and political entrepreneurship were introduced in relation to public administration in the 1960s. Early examples were constructed in relation to institutional change (Eisenstadt, 1964; 1980), the bridging role of the entrepreneur between different spheres in local communities (Barth, 1972), and the carrying out of urban redevelopment and social programs in local government (Dahl, 1961; Murphy, 1971). Although the concepts of entrepreneurship were used later to describe a variety of phenomena (Sheingate, 2003), there are few comparisons of the differences and similarities between early contributions to understand public- and private-sector entrepreneurship. The objective of this paper is to contribute to this discourse by comparing the early contributions of Joseph A. Schumpeter and Robert A. Dahl.